A review of Non-Revenue Water (NRW) for sustainable University campuses / Wan Nur Syazwani Wan Mohammad - Wan Mohammad, Wan Nur Syazwani (2022)
Non-revenue water (NRW) is the summation of unbilled authorized consumption and water losses due to apparent and real losses. Simply put, water that is not used or paid for will affect local economies and locally available recourses. Of late, research on NRW particularly in University Campuses is still an emerging field. Hence, this paper delineates the overview of NRW, a sustainable University Campus, and the benefits of NRW in the University Campus' sustainability through an extensive literature review. From the review, six (6) aspects of NRW (ie., NRW prediction or estimation, the water distribution network, digital tools, NRW management, driver of water losses, and cost-effectiveness of NRW) were discussed in the previous study. While, four (4) categories (i.e., water quality, customer complaints, water resources, and impact on service efficiency and financial management) are listed as benefits of NRW through the NRW reduction program in the sustainability of the University Campus. As a result, this paper is able to provide insight to University Stakeholders for the consideration of NRW in managing water management for sustainable campus development.